RESPON PERTUMBUHAN STEK DAUN LIDAH MERTUA (Sansevieria Parva) PADA PEMBERIAN ZAT PENGATUR TUMBUH SINTETIK (ROOTONE-F) DAN ASAL BAHAN STEK - Susi Sulistiana (Jurnal Matematika Sains dan Teknologi, 2013)
This research aims to study the growth response of plant leaf cuttings mother in-law’s tongue (Sansevieria parva) of various synthetic plant growth regulator treatment (Rootone-F) and origin of cuttings. Experiments performed with 3x3 factorial design with completely randomized design patterns. The first factor is the dose of Rootone-F ZPT which consists of 3 levels: 0 g/cuttings as a control (R0); 0.2 g/cuttings (R1), 0.4 g/cuttings (R2). The second factor is the origin of cuttings, namely the top/tip leaves (B1), the middle leaves (B2), and the bottom/ leaves base (B3). Parameters observed and measured is the experiment percentage of live cuttings, the percentage of rooted cuttings, the percentage of sprouted cuttings, root length, number of roots, root wet weight, and root dry weight. The results showed synthetic plant growth regulator treatment (Rootone-F) to respond to growth parameters leaf cuttings on root length, number of roots, root wet weight, and root dry weight compared with controls. The treatment combination of synthetic plant growth regulator (Rootone-F) 0.4 g/cuttings by cutting material from the middle to give the best results on the parameters of the root, root wet weight, and dry weight, whereas the combination treatment of synthetic plant growth regulator (Rootone-F) 0, 2 g/cuttings by cutting material from the middle to give the best results on the parameters of the plant leaf cuttings root length Sansevieria parva at the end of the experiment. Penelitian ini bertujuan untuk mempelajari respon pertumbuhan stek daun tanaman lidah mertua (Sansevieria parva) terhadap berbagai perlakuan Zat pengatur tumbuh (ZPT) sintetik (Rootone-F) dan asal bahan stek. Percobaan dilakukan dengan Rancangan Faktorial 3x3 dengan pola Rancangan Acak Lengkap (RAL). Faktor I adalah dosis ZPT Rootone-F yang terdiri dari 3 taraf : 0 g/stek sebagai kontrol (R0) ; 0,2 g/stek (R1) ; 0,4 g/stek (R2). Faktor II adalah asal bahan stek, yaitu bagian atas/ujung daun (B1), bagian tengah daun (B2), dan bagian bawah/pangkal daun (B3). Parameter yang diamati dan diukur adalah persentase stek hidup, persentase stek berakar, persentase stek bertunas, panjang akar, jumlah akar, bobot basah akar, dan bobot kering akar. Hasil penelitian menunjukkan perlakuan ZPT sintetik (Rootone-F) merespon pertumbuhan stek daun pada parameter panjang akar, jumlah akar, bobot basah akar, dan bobot kering akar dibanding dengan kontrol. Perlakuan kombinasi ZPT sintetik (Rootone-F) 0,4 g/stek dengan asal bahan stek bagian tengah memberikan hasil yang terbaik pada parameter jumlah akar, bobot basah akar, dan bobot kering, sedangkan perlakuan kombinasi ZPT sintetik (Rootone-F) 0,2 g/stek dengan asal bahan stek bagian tengah memberikan hasil yang terbaik pada parameter panjang akar stek daun tanaman Sansevieria parva pada akhir percobaan.